Time trends in surgical provision and cancer-specific outcomes in patients with stage T2-3 kidney cancer: a SEER-based study - Song, Zhuo; Xing, Jizhang; Sun, Zhijia; Kang, Xiaoli; Li, Hongzhao; Ren, Gang; Wang, Yingjie (Frontiers in Surgery, 2024)
Surgery is the primary therapy that crucially affects the survival of patients with kidney cancer (KC). However, pertinent surgical decision criteria for individuals with stage T2-3 KC are lacking. This study aimed to display the practical choices and evolving trends of surgical procedures and elucidate their implied value.Through the Surveillance, Epidemiology, and End Results (SEER) dataset, the levels and evolving trends of different surgical methods were examined to determine cancerspecific risk of death (CSRD). Additionally, stratification analysis and survival rate analysis were performed to explore the effectiveness of partial nephrectomy (PN).In this study, 9.27% of patients opted for PN. Interestingly, an upward trend was observed in its decision, with an average annual percentage change (AAPC) of 7.0 (95% CI: 4.8-9.3, P < 0.05). Patients who underwent PN and were in a relatively less severe condition exhibited more favorable CSRD levels (0.17-0.36 vs. 0.50-0.67) and an improvement trend compared with those who underwent radical nephrectomy (RN)